Impact of intensive care practices on short-term and long-term outcomes for extremely preterm infants: comparison between the British Isles and France. - Bodeau-Livinec, F; Marlow, N; Ancel, P; Kurinczuk, J; Costeloe, K; Kaminski, M (2008)
OBJECTIVES: The objective of this study was to compare practices of care and outcomes of infants who were born between 23 and 25 weeks' gestation in 1995 in the British Isles and in 1997-1998 in France. METHODS: We examined 2 population-based cohorts in the British Isles (1892 births included) and in France (456 births): the EPICure and EPIPAGE studies. The rate of follow-up was 90% at 30 months and 86% at 2 years. At 5 to 6 years, the cognitive function of 64% of the children without severe disability was assessed in the EPICure study and 57% in the EPIPAGE study. RESULTS: The mortality rate of live-born infants was lower in the EPICure study (25%) than in the EPIPAGE study (34%) before admission to a NICU but higher in the NICU (45% vs 29%, respectively), such that there was no difference in the proportions of survivors at discharge after adjustment for gestational age. The risk for severe brain lesions was 24% among infants who were admitted to a NICU in both studies, 41% in the EPICure study versus 67% in the epidemiologic study on great prematurity (EPIPAGE) among infants who died after discontinued treatment in NICU, and 17% vs 11% among survivors at discharge. The risk for cerebral palsy at 24 to 30 months was 20% in the EPICure study versus 16% in the EPIPAGE study, whereas the risk for overall cognitive score of <70 at 5 to 6 years was 10% vs 14%, respectively. CONCLUSIONS: Despite apparent differences in the modalities of limitation of intensive care, the outcomes of infants who were born at 23 to 25 weeks' gestation in the EPICure and EPIPAGE studies were not significantly different.